ROLE OF METHYLPREDNISOLONE IN EARLY PREDICTED DIPHTHERIC CARDIOMYOPATHY IN CHILDREN: IS THIS A SOLUTION? - Rashid, Usman; Nawaz , Rashid; Sheikh , Saifullah; Bajwa, Fazal Ilahi; Fatima, Zile (Journal of Ayub Medical College Abbottabad, 2022)
Background: Diphtheria remains an important cause of paediatric mortality in developing countries. The mortality rate is still ˆ¼10% and has changed little over the past 20 years with particular reference to developed world. The objective of this study is to examine clinical spectrum of diphtheric cardiomyopathy and by using tools (serum markers, ECG, Echocardiography) to predict the cardiomyopathy and role of steroids in these predicted patients. Methods: For this cohort study, 67 patients having diphtheria presenting for the first time in a 3-year period were enrolled after obtaining informed verbal consent from the guardian of each child. Demographical profile, vaccination status, clinical spectrum, ECG interpretation and echocardiographic findings were recorded that predicted the occurrence of diphtheric cardiomyopathy and used intravenous methylprednisolone pulses in these predicted patients to look for their outcome regarding change in severity or the fate in the form of mortality. Results: Among the 67 enrolled children (M: F 2.3:1) with age ranging from 24 to 172 months (median 106 months), 56.7% subjects presented with diphtheria were non-vaccinated. 37.3% had a cardiac involvement in the form of diphtheria cardiomyopathy or arrhythmia.7.5% patient expired on follow up. Presence of septal paradoxes on echo had association with the cardiac involvement (OR 10.1: 95% CI 1.2-84.6; p=0.0005). IV methyl prednisolone was given in all 37.3% (n=25) patients predicted as diphtheric cardiomyopathy (Asymptomatic) and 88 %(n=22) had a favourable outcome with no morbidity and mortality. 12% (n=3) were expired and they presented with shock and VT as their first presentation (symptomatic). Conclusion: Early prediction by alone or in combination of ECG and echocardiographic markers and early use of IV methyl prednisolone in these predicted patients before symptoms, can reduce the mortality related to diphtheric cardiomyopathy and can decrease the burden of the disease in the community. Further randomized controlled trials with a larger sample size are required to unambiguously delineate the prognostic value of steroids in early predicted diphtheric cardiomyopathy.